Optical fibre-based methodology for screening the effect of probiotic bacteria on conjugated linoleic acid (CLA) in curdled milk - Silva, Lurdes I. B. (2012)
A methodology based on optical fibre (OF) detection was developed for screening the potential of CLA production by Lactobacillus casei-01, Lactobacillus acidophilus La-5 and Bifidobacterium lactis B94 in probiotic curdled milk. The OF based methodology was validated by comparison with an analytical method based on gas chromatography-mass spectrometry (GC-MS) and it showed comparable linearity (between 5 and 130 mu g), accuracy and detection limits, which ranged from 1.92 to 2.56 mu g for CLA methyl ester and oleic acid methyl ester, respectively. Furthermore, the proposed OF based methodology was an advantageous analytical methodology for screening CIA production in probiotic curled milk, due to its compact design and effective cost of analysis. The application of the OF analytical method allowed to detect CLA in the probiotic curdled milk: the production of CLA by probiotic enzymes reached values of 297 +/- 19 mu g g(-1) by 60 days of ripening unfolding this potential functional food as very interesting from a technological point of view.